2002
DOI: 10.1073/pnas.092131899
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite transport by mammalian aquaglyceroporins AQP7 and AQP9

Abstract: Much is known about the transport of arsenite and antimonite into microbes, but the identities of mammalian transport proteins are unknown. The Saccharomyces cerevisiae FPS1 gene encodes a membrane protein homologous to the bacterial aquaglyceroporin GlpF and to mammalian aquaglyceroporins AQP7 and AQP9. Fps1p mediates glycerol uptake and glycerol efflux in response to hypoosmotic shock. Fps1p has been shown to facilitate uptake of the metalloids arsenite and antimonite, and the Escherichia coli homolog, GlpF,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
304
0
7

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 458 publications
(315 citation statements)
references
References 49 publications
(61 reference statements)
4
304
0
7
Order By: Relevance
“…However, in the arsenic uptake and cytotoxicity assay, the OATP-C increased uptake and cytotoxicity of arsenic was not as much as that of E 2 17bG. It is possible that there are other pathways for arsenic uptake by cells other than OATP-C [28,29,41]. For example, Hung and Lee [41] indicated that As III can be freely taken up by cells through simple diffusion, and As V shares a common transport system with phosphate in cells.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, in the arsenic uptake and cytotoxicity assay, the OATP-C increased uptake and cytotoxicity of arsenic was not as much as that of E 2 17bG. It is possible that there are other pathways for arsenic uptake by cells other than OATP-C [28,29,41]. For example, Hung and Lee [41] indicated that As III can be freely taken up by cells through simple diffusion, and As V shares a common transport system with phosphate in cells.…”
Section: Discussionmentioning
confidence: 94%
“…For example, Hung and Lee [41] indicated that As III can be freely taken up by cells through simple diffusion, and As V shares a common transport system with phosphate in cells. On the other hand, recent reports have shown that AQP9 and AQP7 can cause uptake of arsenite into mammalian cells [28].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, a chromate-tolerant mutant of S. cerevisiae accumulates lower amounts of Cr than the WT [33,34]. In addition, we have shown that either decreasing As(III) uptake by deletion of FPS1 [35] or increasing efflux by induction of ACR3 [36] will confer As(III) tolerance in S. cerevisae. To examine whether the increased As(III) tolerance of Y800-Ntcyc07 is related to alteration of the steady state levels of arsenic, the amount of arsenic was measured in cells cultured for 24 h in ura(À) CM medium with 50 lM sodium arsenite (Fig.…”
Section: Cloning and Characterization Of The Tobacco Gene Ntcyc07mentioning
confidence: 95%
“…Although not previously related to PD, several lines of evidence argue for a link between these. AQP9 is an aquaglyceroporin with particularly broad substance permeability, transporting water, glycerol, monocarboxylates and arsenite, among others (10)(11)(12)(13)(14). This water channel has recently been found to be selectively expressed in dopaminergic plasma membranes as well as mitochondrial inner membranes in the SN (15)(16)(17), indicating that it may serve as a toxin influx route into these cells, thereby accounting for an increased susceptibility to cell death.…”
mentioning
confidence: 99%